The effect of road traffic noise to high-rise residential located adjacent to highway / Jumriani Hasanuddin - Hasanuddin, Jumriani (Faculty of Architecture,Planning and Surveying, 2015)
In the year of 1999, there were more than 1,000 vehicles including buses, lorry cars and motorbikes in Selangor. These numbers are increasing every year. In the same time, the noise generated by all the vehicles above is increasing also. Noise that generated by vehicles in Selangor should be concerned by determine the stage of noise pollution. A study was conducted to determine the noise level generated by vehicles at highway adjacent to high-rise residential, which are Saujana Residency Condominium,Subang, Mentari Court Apartment, Petaling Jaya and Subang Avenue Condominium Subang in Selangor. Sound Level Meter was and data collected in three days every case study. The noise compared to the standard by World Health Organization (WHO). The result indicated that the value of noise generated by vehicles in every three case study exceed the value regulated by WHO. It shows that three-location case study is did not safe from noise pollution.